Participation of Farmer Group Members in Designing Extension Programs on Tomato Farming - Muhammad Salim; Ullyasniaty Ullyasniaty; Rayuddin Rayuddin (Agrisurya, 2022)
The objective of this study was to describe the participation of farmer group members in the preparation of an extension program on tomato farming in Wowasolo Village, Wongeduku District, Konawe Regency. The research method is to determine the population and sample in one of the farmer groups that cultivate tomatoes. The number of samples that were set was 30 people from all members of the vegetable farmer group, which were selected by random sampling. Analysis of the data used is Likert Scale analysis. The results of the research obtained in the field regarding the participation of farmer group members in the extension program are that there are four stages of farmer group participation in the extension program, namely: first; the planning stage obtained an average value of 2.47 with the category of High (T), second; the implementation stage the average value is 4.39 with the category of High (T), third; the utilization stage has an average value of 2.23 with high (T) and fourth categories; evaluation stage the average value is 3.19 with the High category (T). The dominant participation factor is influenced by the willingness, the opportunity and the desire to add experience in tomato farming. Low farmer education and community habits with conventional farming systems are limiting factors for participation in agricultural extension programs.